Environmental and natural resource economics : an encyclopedia - Haab, Timothy C.; Caviglia, Jill L., 1970-; Haab, Timothy C., 1969-; Whitehead, John Claiborne, 1963- (Santa Barbara, California : Greenwood, an imprint of ABC-CLIO, LLC, 2014)
""Accessible to students and practitioners without an advanced degree in environmental economics, this essential reference work pinpoints the role of the economy in both creating and solving many of the world's most pressing environmental challenges""--
Includes index.
Includes bibliographic references and index.
Keywords: Environmental economics -- Encyclopedias; Natural resources -- Encyclopedias